Penurunan Kejadian Loss to Follow up Melalui Pemberian SMS Reminder dan Edukasi Pasien HIV/AIDS - Ekta Suci Wahyuni; Rohman Azzam (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
HIV / AIDS treatment programs have resulted in reduced HIV-related morbidity and mortality. In addition to understanding the factors associated with loss to follow-up, interventions are also needed to prevent it. The purpose of this study was to determine the reduction in the incidence of loss to follow up by giving SMS reminders and educating HIV / AIDS patients. This type of research is a quantitative study with a quasi experimental design with a pre-test and post-test approach with a control group on 36 patients who have been doing LTFU at the Bekasi District Hospital. Descriptive analysis was carried out to see the characteristics of the respondents. Bivariate analysis was carried out to assess changes that occurred after the SMS Reminder and education interventions were given. The results of this study indicate that age, sex, occupational status and education level are associated with loss to follow-up, while duration of infection and distance from home to health care providers are not associated with loss to follow-up. There was a significant change in loss to follow-up after two interventions were given. Keywords: education; educational events; loss to follow up; SMS reminder ABSTRAK Program pengobatan HIV/AIDS telah menghasilkan penurunan morbiditas terkait HIV dan kematian. Selain pemahaman faktor-faktor yang terkait dengan loss to follow up, perlu dilakukan juga intervensi untuk pencegahannya. Tujuan penelitian ini adalah untuk mengetahui penurunan kejadian loss to follow up melalui pemberian SMS reminder dan edukasi pasien HIV/AIDS. Jenis penelitian ini merupakan penelitian kuantitatif dengan desain eksperimental kuasi dengan pendekatan pre-test and post-test with control group terhadap 36 pasien yang selama ini melakukan LTFU di RSUD Kabupaten Bekasi. Analisis deskriptif dilakukan untuk melihat karakteristik responden. Analisis bivariat dilakukan untuk menilai perubahan yang terjadi setelah diberikan intervensi SMS Reminder dan edukasi. Hasil penelitian ini menujukkan bahwa usia, jenis kelamin, status pekerjaan dan tingkat pendidikan berhubungan dengan kejadian loss to follow up, sedangkan lama terinfeksi dan jarak dari rumah ke tempat pelayanan kesehatan tidak berhubungan dengan loss to follow up. Terjadi perubahan loss to follow up bermakna setelah diberikan dua intervensi. Kata kunci: edukasi; kejadian edukasi; loss to follow up; SMS reminder